Metabolic engineering interventions for sustainable 2,3-butanediol production in gas fermenting Clostridium autoethanogenum - Ghadermazi, Parsa, author; Chan, Siu Hung, advisor; Wrighton, Kelly, committee member; Reisfeld, Brad, committee member (Colorado State University. Libraries, 2023)
Gas fermentation provides a promising platform to turn low-cost and readily available single-carbon waste gases into commodity chemicals such as 2,3-butanediol. Clostridium autoethanogenum is usually used as a robust and flexible chassis for gas fermentation. Here, we leveraged on constraints-based stoichiometric modeling and kinetic ensemble modeling of the C. autoethanogenum metabolic network to provide a systematic in silico analysis of metabolic engineering interventions for 2,3-butanediol overproduction and low carbon substrate loss in dissipated CO2. Our analysis allowed us to identify and to assess comparatively the expected performances for a wide range of single, double, and triple interventions. Our analysis managed to individuate bottleneck reactions in relevant metabolic pathways when suggesting intervening strategies. Besides recapitulating intuitive and/or previously attempted genetic modifications, our analysis neatly outlined that the interventions - at least partially - impinging on by-products branching from acetyl-CoA and pyruvate (acetate, ethanol, amino acids) offer valuable alternatives to the interventions focusing directly on the specific branch from pyruvate to 2,3-butanediol.
Zip file contains supplementary files 1 and 2.
Keywords: metabolic engineering; C. autoethanogenum